Environmental risk assessment in a contaminated estuary: An integrated weight of evidence approach as a decision support tool. (1st July 2017) - Caeiro, S.; Vaz-Fernandes, P.; Martinho, A.P.; Costa, P.M.; Silva, M.J.; Lavinha, J.; Matias-Dias, C.; Machado, A.; Castanheira, I.; Costa, M.H.
Abstract: Environmental risk assessment of complex ecosystems such as estuaries is a challenge, where innovative and integrated approaches are needed. The present work aimed at developing an innovative integrative methodology to evaluate in an impacted estuary (the Sado, in Portugal, was taken as case study), the adverse effects onto both ecosystem and human health. For the purpose, new standardized lines of evidence based on multiple quantitative data were integrated into a weight of evidence according to a best expert judgment approach. The best professional judgment for a weight of evidence approach in the present study was based on the following lines of evidence: i) human contamination pathways; ii) human health effects: chronic disease; iii) human health effects: reproductive health; iv) human health effects: health care; v) human exposure through consumption of local agriculture produce; vi) exposure to contaminated of water wells and agriculture soils; vii) contamination of the estuarine sedimentary environment (metal and organic contaminants); viii) effects on benthic organisms with commercial value; and ix) genotoxic potential of sediments. Each line of evidence was then ordinally ranked by levels of ecological or human health risk, according to a tabular decision matrix and expert judgment. Fifteen experts scored two fishing areas of the Sado estuary and a control estuarine area, in a scale of increasing environmental risk and management actions to be taken. The integrated assessment allowed concluding that the estuary should not be regarded as impacted by a specific toxicant, such as metals and organic compounds hitherto measured, but by the cumulative risk of a complex mixture of contaminants. The proven adverse effects on species with commercial value may be used to witness the environmental quality of the estuarine ecosystem. This method argues in favor of expert judgment and qualitative assessment as a decision support tool to the integrative management of estuaries. Namely it allows communicating environmental risk and proposing mitigation measures to local authorities and population under a holistic perspective as an alternative to narrow single line of evidence approaches, which is mandatory to understand cause and effect relationships in complex areas like estuaries. Highlights: A weight of evidence approach was used based on 9 lines of evidence and best professional judgment. An integrated environmental risk assessment was proposed combining ecological and human health risk. Expert judgment is helpful as a decision support tool for integrative management of estuaries. Sado Estuary in Portugal was used as case study.